2014
DOI: 10.1182/blood.v124.21.3085.3085
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Early Efficacy in an Ongoing Pilot Study of Brentuximab Vedotin and AVD Chemotherapy Followed By 30 Gray Involved-Site Radiotherapy for Newly Diagnosed, Early Stage, Unfavorable Risk Hodgkin Lymphoma

Abstract: Background: Brentuximab vedotin has not been previously studied in combination with combined modality therapy for the frontline treatment of early stage Hodgkin lymphoma. We designed a pilot study to assess the safety and early efficacy of four cycles of brentuximab vedotin (BV) + AVD chemotherapy followed by 30 Gray involved-site radiotherapy (ISRT) for the treatment for early stage, unfavorable risk HL. Methods: Patients with newly diagnosed, stage I/II, classical HL with unfavorable risk prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This will become even more relevant as new chemotherapy regimens are introduced, utilizing new drugs such as Brentuximab vedotin. 31 , 32 …”
Section: Discussionmentioning
confidence: 99%
“…This will become even more relevant as new chemotherapy regimens are introduced, utilizing new drugs such as Brentuximab vedotin. 31 , 32 …”
Section: Discussionmentioning
confidence: 99%
“…Thus far, a preliminary study of ABrenVD in early stage unfavorable Hodgkin lymphoma (but also including several patients with more advanced disease) showed that 14/15 patients achieved a negative PET CT scan after 2 cycles including 10/10 with bulky mediastinal disease [22] . Although 30 Gy adjuvant radiation was given without any signal thus far for pulmonary toxicity, it is expected that if other ongoing trials confirm the superiority of the brentuximab-containing regimen, trials with reduced or no RT will undoubtedly be tested.…”
Section: Improving Cure Ratesmentioning
confidence: 99%